The Influence of Hedonic Shopping Value, Sales Promotion and Serendipity Information on Impluse Buying Behavior with Urge to Buy Impulsively as a Mediating Variable among Tiktok Shop Users (A Study on the Purchase of "Top Purchase Categories" Products on Pontianak) - Octaviani, Dewi Sinthia; Pebrianti , Wenny; Purmono, Bintoro Bagus (International Journal of Economic, Finance and Business Statistics, 2024)
This study intends to investigate the impact of hedonic shopping value, sales promotion, and serendipity information on impulse buying behavior, with the urge to buy impulsively acting as a mediator, among users of TikTok Shop in Pontianak. We employ a quantitative and associative causal approach. Our study aims to include all individuals who use the TikTok Shop platform as our target population. The research was conducted from September 2023 to March 2024, involving 210 participants who were chosen using purposive sampling techniques. Data analysis was performed using SEM with AMOS. The findings suggest that hedonic shopping value, sales promotion, and serendipity information all have a notable impact on urge to buy impulsively. Additionally, hedonic shopping value, serendipity information, and urge to buy impulsively also significantly influence impulse buying behavior, whereas sales promotion does not. Urge to buy impulsively mediates the relationship between hedonic shopping value and serendipity information with impulse buying behavior, but not between promotional offers and impulsive buying behavior.